2022-LBA-789-ESGO Sentinel lymph node detection with Magtrace® in endometrial cancer. (27th October 2022) - Jedryka, Marcin; Kryszpin, Marcin; Czekanski, Andrzej; Lepka, Piotr; Klimczak, Piotr
Abstract : Introduction: This prospective observational study, named SENDOCAN (S entinel lymph node detection with Magtrace® in Endo metrial Can cer) evaluates the efficacy of the Magtrace® system in SLN (Sentinel Lymph Nodes) detection in endometrial cancer patients with unsuspicious lymph nodes in comparison with the standard of care. The nanoparticle paramagnetic detection systems of SLN have been prooved so far to be comparable and non-inferior to the standard procedure of systematic lymphadenectomy in breast cancer and vulvar cancer patients. Methods: 30 patients with endometrial cancer presumably stage I, with unsuspicious lymph nodes were included into the study and received a cervical injection of superparamagnetic iron oxide tracer (Magtrace®) which localized and detected SLN with magnetic counts and with visual inspection for their brownish colour. For each SLN the anatomic site, magnetic counts and colour was documented before biopsy. Afterwards, systematic lymphadenectomy – pelvic (PLND) and paraaortic (PALND) was performed as the standard of care. Results: SLN were detected in every patient. Bilateral SLN were found in 70% of cases. The mean SLN count per patient was 1.7. 94% of SLN were assessed as brownish stained. Micrometastases were detected in 4 SLN, confirmed by PLND/PALND. However, in 2 cases micrometastases were detected in paraaortic lymph nodes during PALND but not with SLNB. Statistic results have been presented in the table. Conclusions: The study showed efficient Magtrace® detection of SLN in endometrial cancer patients regarding the pelvic lymph nodes. This cannot be confirmed when paraortic lymph nodes are involved.